AGORA XI - the learning region. Thessaloniki, 15 to 16 March 2001 : Thessaloniki, 15 to 16 March 2001 - (:unkn) unknown (Office for Official Publications of the European Communities, 2003)
"The region or local area is too often felt to be the focus of every kind of conservatism, folklore and vote-catching. At this Agora, we questioned this image of the region and re-examined and redefined what was actually meant by region. The region, in our notion of the learning region, has a variable geometry. It has more to do with what we could call the 'local level' than with the administrative notion of the region. The region is defined by sets of partners and institutions which try to work together locally for the economic and social developments of its inhabitants. The region is defined more by the fabric of links which are established there and by collectively agreed projects than by its purely geographical frontiers. It must nevertheless continue to have a human dimension: the citizens' day-to-day problems must always be kept in sight. The role of the region, redefined in this way, as a driving force behind the promotion of social, educational and occupational innovation was highlighted and illustrated in detail. This Agora nevertheless also took pains to stress that local powers needed to be counterbalanced by national or supranational powers. This will allow a degree of balance between the resources and endeavours of regions with differing natural and human assets. The aim is to ensure overall cohesion, rising above local temptations and deceptions." (Verlag, BIBB-Doku)
Keywords: G 2.1.4 Regionalisierung; S 2.4.2 Regionalentwicklung; I 2.2 Europa; Region; Lernende Region; Regionales Netzwerk; Europa